PERILAKU BERAGAMA PEREMPUAN NGOREK DI PESISIR LAMONGAN - Farihah, Irzum (Sawwa: Jurnal Studi Gender, 2019)
This study aims to look at the religious behavior of fish sorting women laborers in the coastal area of Lamongan. This research uses a descriptive qualitative method, with observation and in-depth interviews with fish sorting women laborers, boat owners and the Head of fishermen association. Data were analyzed using the Miles-Huberman model with stages of data collection, data reduction, data presentation, and conclusions. This article produces that: first, the understanding of religious women is inseparable from their belief in things that are transcendent able to move worldly life, by applying in daily behavior in the workplace by maintaining an honesty attitude, still carrying out prayer and in their social environment while maintaining friendly relations by adjusting the traditions that run in the community. Second, various social actions that can be taken can be seen from instrumental rationality, value rationality, affective rationality, and traditional rationality.